Complex marine bioturbation ecosystem engineering behaviors persisted in the wake of the end-Permian mass extinction - Cribb, Alison T. (Sci Rep, 2020)
The end-Permian mass extinction was the most severe mass extinction event of the Phanerozoic and was followed by a several million-year delay in benthic ecosystem recovery. While much work has been done to understand biotic recovery in both the body and trace fossil records of the Early Triassic, almost no focus has previously been given to analyzing patterns in ecosystem engineering complexity as a result of the extinction drivers. Bioturbation is a key ecosystem engineering behavior in marine environments, as it results in changes to resource flows and the physical environment. Thus, the trace fossil record can be used to examine the effect of the end-Permian mass extinction on bioturbating ecosystem engineers. We present a dataset compiled from previously published literature to analyze burrowing ecosystem engineering behaviors through the Permian-Triassic boundary. We report two key observations: first, that there is no loss in bioturbation ecosystem engineering behaviors after the mass extinction, and second, that these persisting behaviors include deep tier, high-impact, complex ecosystem engineering. These findings suggest that while environmental conditions may have limited deeper burrowing, complex ecosystem engineering behaviors were able to persist in the Early Triassic. Furthermore, the persistence of deep tier bioirrigated three-dimensional network burrows implies that benthic biogeochemical cycling could have been maintained at pre-extinction states in some local environments, stimulating ecosystem productivity and promoting biotic recovery in the Early Triassic.